PROBLEMS OF ASSESSING TRANSBOUNDARY AND INTERREGIONAL ATMOSPHERIC AIR POLLUTION IN THE REGIONS OF UKRAINE (INNOVATIVE ECONOMY, 2023)
Samko O.O. PROBLEMS OF ASSESSING TRANSBOUNDARY AND INTERREGIONAL ATMOSPHERIC AIR POLLUTION IN THE REGIONS OF UKRAINEPurpose. The aim of the article is to research and adapt existing methods of assessment of transboundary and interregional transfer of pollutants in the context of the interaction of countries and individual regions within an individual country to conditions of limited input data.Methodology of research. The following scientific methods were used in the process of scientific research: methods of abstraction and generalization – for the study of theoretical foundations and existing approaches to the essence of transboundary ecological security and transboundary (interregional) atmospheric air pollution in particular; system analysis – to substantiate the simplified methodology for assessing the maximum possible dangerous impact on the atmospheric air of the region from stationary sources of atmospheric air pollution in adjacent territories; methods of analysis and synthesis – to identify adjacent territories that pose the greatest threat from the point of view of interregional atmospheric air pollution, and to assess such an impact. Findings. A distinction between the concepts of “transboundary pollution” and “interregional pollution” of atmospheric air is proposed. The use of a simplified methodology for assessing transboundary (interregional) atmospheric air pollution in the region is substantiated.Originality. An algorithm for assessing possible interregional (transboundary) atmospheric air pollution of the region based on the adaptation of existing methods is proposed.Practical value. The proposed algorithm and adapted methodology for assessing possible interregional (transboundary) atmospheric air pollution of the region can be applied at the level of all regions when developing regional programs in the direction of atmospheric air protection, at the level of interstate cooperation in the field of cross-border cooperation, as well as for the development and adoption of operational decisions with in order to quickly respond to the current situation.Key words: transboundary environmental safety, transboundary pollution, transboundary transfer of pollutants, interregional air pollution.
Keywords: cross-border ecological safety; cross-border pollution; cross-border transfer of pollutants; interregional atmospheric air pollution